Effect of long-term low dose prednisolone administration on bone mineral density: Relating to non-compliant women with rheumatoid arthritis - Behzad Heidari; Parnaz Heidari; Karimollah Hajian-Taliki; Mohammadali Bayani; Mansour Babaei (Babol University of Medical Sciences, 2018)
Background: Long-term treatment of rheumatoid arthritis (RA) with prednisolone (PRED) is associated with bone mineral density (BMD) loss. This study aimed to determine the status of BMD in non-compliant women who used PRED alone for RA. Methods: Non-adherent RA taking < 7.5 mg daily PRED without DMARDs for > 6 months, and RA patients taking methotrexate +PRED (RA control) were compared with age-matched non-RA controls. BMD was measured by dual energy x-ray absorptiometry (DXA) method and osteoporosis (OP) was diagnosed by WHO criteria. Influence of PRED on RA bone mass, and the risk of OP in RA  was assessed by comparing PRED users RA and RA control,versus non-RA controls. Results: Sixty-four PRED user RA, 39 RA controls and 111 non RA-controls, with respective mean (±SD) age of 52±11; 8, 51±11; and 52±7.5 years (p=0.91) were studied. Median duration of treatment in PRED users and RA control was 2.5 and 4 years, respectively. BMD g/cm2 at the femoral neck (FN-BMD) and lumber spine (LS-BMD) in PRED users and RA control was significantly lower than non-RA control (P=0.001). The prevalence of OP at either FN or LS in both RA groups was significantly higher than controls (P=0.001). In PRED users, the risk of OP increased by OR=4.9, P=0.001) and in RA controls by OR=1.7 (P=0.20). The risk of OP in PRED user RA was 2.89 times (P=0.014) greater than RA controls. Conclusions: These findings indicate significantly lower BMD, and higher prevalence of osteoporosis in non-compliant women with RA taking low-dose PRED alone for a median period of 2.5 years, as compared with patients taking standard treatment comprising methotrexate +PRED.